The Effectiveness of Picture Story Media in Improving Early Childhood Cognitive Abilities at TKN Beiposo - Maria Oncilia Weti; Andi Nafsia; Elisabeth Tantiana Ngura; Konstantinus Dua Dhiu (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
This study aims to determine the extent to which picture story media is effective in improving early childhood abilities at TKN Beiposo. The research method used was a pre-experimental design with a one-group pretest–posttest design. The research subjects were children in group B1 aged 5–6 years at TKN Beiposo. Data were collected through pretest and posttest, then analyzed using a paired sample t-test. Based on descriptive statistical results, children's cognitive abilities before treatment (pretest) had a mean score of 18.07 with a standard deviation of 5.08 and a standard error of 1.31 from a total sample of 15 children. This value indicates that children's cognitive abilities at the initial stage were relatively low and showed variation among individuals. After being given treatment in the form of learning using picture story media, the average cognitive ability score in the posttest increased to 36.00, with a standard deviation of 6.05 and a standard error of 1.56, indicating a significant improvement in cognitive abilities after the intervention. Thus, child-friendly picture story media has proven to be effective and can be used as an alternative learning medium that is innovative, engaging, and appropriate to the characteristics of early childhood.